The Ethical Challenges in Modern Media with a Focus on Addressing Fake News and Protecting Privacy - كتاب, محمد راتب; ياسين, ضرغام سالم (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
In the modern media age, the ethical challenges facing the media cannot be ignored. Among these challenges, issues such as the spread of fake news and the need to protect individuals' privacy stand out. Dealing effectively with these challenges requires directing efforts toward a deeper understanding of the ethical impacts of media behaviors and developing a strong ethical framework that guides their work and limits privacy violations and the spread of misinformation. The spread of fake news represents a major challenge to media ethics, as this news can lead to distortion of facts and a negative impact on public opinion and political and social decisions. With increasing reliance on the Internet and social media, protecting privacy has become one of the main ethical challenges in the media field the collection and use of personal data without the consent of its owner raises important privacy issues, which requires the development of laws and policies that protect the privacy of individuals and ensure that data is used ethically and transparently.